GOLD AND PLATINUM GROUP METALS IN SKARNS OF THE OL'GINSK AND DAL'NEGORSK ORE DISTRICTS OF PRIMORYE AND SOME ISSUES OF METALLOGENY OF THE SOUTHERN SIKHOTE ALIN REGION - Kazachenko V.T.; Perevoznikova E.V.; Miroshnichenko N.V.; Karabtsov A.A.; Solyanik V.A. (My University, 2007)
The Triassic–Jurassic carbonaceous sequence of Sikhote Alin includes metalliferous sediments represented by siliceous–rhodochrosite rocks and their metamorphosed analogues, siliceous rocks with pyrophanite (“brown cherts”), tin–iron ores, “ilmenitebiotite–feldspar” (metamorphosed clayey) rocks, and “itabirites.” They are characterized by high contents of Au, Ag, Pt, and Pd and the ubiquitous presence of minerals of these elements. Hydrothermally altered sandstones, as well as siliceous–clayey and siliceous rocks, which are associated with syngenetic metalliferous rocks, contain grains of gold, silver, argentite, platinum, Pd-platinum, itenbohaardite, and other minerals of noble metals. It should be mentioned that identifications of all minerals mentioned in this paper have been confirmed by microprobe analyses. Another type of hydrothermal ores is represented by Mn-rich amphibole–pyroxene rocks that contain native gold, silver, Pd-platinum, and other minerals of gold, silver, and platinum group metals (PGM).
Keywords: Mesozoic::Triassic; Mesozoic::Jurassic; Мезозой::Триасовая; Мезозой::Юрская